Automation of data analysis and presentation through GUI in Windows environment - Li, Jing. (2008)
This dissertation discusses the design and development of a user-friendly software application that can automatically perform complex data analysis, provides flexible user controls and able to deliver professional data presentations used in formation evaluation for OIIP determination.